When a lost "Petit Prince" meets Antoine de Saint Exupéry: An anthropological case report. (March 2019) - Costedoat, Caroline; Adalian, Pascal; Bouzaid, Eric; Martinet, Annick; Vanrell, Luc; von Gartzen, Lino; Castellano, Philippe; Signoli, Michel; Tzortzis, Stéfan; Stevanovitch, Alain
Highlights: In searching for Antoine de Saint-Exupery, the author of the Petit Prince, we found a real lost little Prince of the WWII. Genetic challenge and DNA profile identification from bones remains. Interdisciplinary approach and assembly of fragmented data as pieces of a puzzle to reconstruct the final story. Symbolism of this study with the identification and restitution of the remains of a German Luftwaffe student pilot. Abstract: This case study reports the anthropological analysis of bones remains discovered on Riou Island (Marseille, France) and the story of two World War II fighter pilots. The discovery of bones on " The Fountain of the Greeks " square on Riou Island occurred in the 1960's and a first anthropological study described a 35-year-old man, about 1.77 m tall, buried since an estimated period between the 13th and 16th centuries. The case was "closed" and the bones were considered as isolated archaeological remains. Few years later, near the coasts of Riou Island, parts of two planes were discovered. One was from of a German Messerschmitt Bf 109 F-4 of the Luftwaffe piloted by Prince Alexis fürst zu Bentheim und Steinfurt, and the other from a French P-38 Lightning F-5 B piloted by Antoine de Saint-Exupery. Therefore, the identification of the skeletal remains mentioned above was then thought to be perhaps one of the two World War II pilots. In this particular context we performed forensic and molecular biology analyses to resolve this identification.